2019－2020年ベルギー南極観測隊による東南極ナンセン氷原における隕石探査報告 - Goderis, Steven; Yesiltas, Mehmet; Pourkhorsandi, Hamed; 白井, 直樹; シライ, ナオキ; Poudelet, Manu; Leitl, Martin; 山口, 亮; ヤマグチ, アキラ; Debaille, Vinciane; Claeys, Philippe; Shirai, Naoki; et al. (国立極地研究所, 2021)
2019－2020 年の夏期に，東南極セール・ロンダーネ山地南部においてベルギー南極観測隊（BELARE）により隕石探査を実施した．ナンセン氷原には，2020 年1 月15 日から2 月6 日まで23 日間滞在し，採取した隕石の総数は66 個，合計重量は約8 kg であった．ナンセン氷原での隕石集積機構を解明するために，隕石の他に氷，火山灰層や岩石の破片も採取した．採取した隕石は，凍結したまま国立極地研究所に輸送された．これら採取した隕石が国際隕石学会の隕石命名委員会に認可された後，分類データはMeteorite Newsletter で公開される． This report summarizes the Belgian Antarctic Expedition (BELARE) 2019－2020 meteorite search and recovery expedition near the Sør Rondane Mountains of East Antarctica during the 2019－2020 field season. This expedition took place from 15 January to 6 February 2020 within the area defined as ＂C＂ of the Nansen Ice Fields (S72°38'−72°48'S, 24°35'−25°06'E). The expedition team consisted of four scientists and two field guides, who systematically searched the ice field area and collected 66 meteorites. The total weight of the meteorites was determined to be ～8 kg. In addition to meteorites, blue ice samples, volcanic ash layers, and wind-blown terrestrial rock fragments were collected from the area to study in detail the nature of the mechanisms concentrating meteorites on the Nansen Ice Fields. The recovered meteorites were transported in a frozen state to the National Institute of Polar Research, Japan for dry-thawing and subsequent classification. departmental bulletin paper